Validation of the Chinese version of the diabetes health profile to predict the impact of mobile health education on quality of life in type 2 diabetes patients - Lyu, Xiaokang; Zeng, Jinmei; Lin, Jingna; Song, Yixuan; Yang, Tingting; Hou, Wenjing (Frontiers in Public Health, 2024)
The Diabetes Health Profile (DHP18), initially created in the United Kingdom, currently lacks a Chinese version. This study endeavors to authenticate the Chinese adaptation of the DHP18 and assess the influence of mobile health (mHealth) education intervention on the quality of life of individuals living with diabetes.